Transforming monosaccharides: Recent advances in rare sugar production and future exploration - Shin-ichi Nakakita; Jun Hirabayashi (BBA Advances)
Rare sugars are defined as monosaccharides and their derivatives that do not exist in nature at all or that exist in extremely limited amounts despite being theoretically possible. At present, no comprehensive dogma has been presented regarding how and why these rare sugars have deviated from the naturally selected monosaccharides. In this minireview, we adopt a hypothesis on the origin and evolution of elementary hexoses, previously presented by one of the authors (Hirabayashi, Q Rev Biol, 1996, 71:365–380). In this scenario, monosaccharides, which constitute various kinds of glycans in nature, are assumed to have been generated by formose reactions on the prebiotic Earth (chemical evolution era). Among them, the most stable hexoses, i.e., fructose, glucose, and mannose remained accumulated. After the birth of life, the “chemical origin” saccharides thus survived were transformed into a variety of “bricolage products”, which include galactose and other recognition saccharides like fucose and sialic acid through the invention of diverse metabolic pathways (biological evolution era). The remaining monosaccharides that have deviated from this scenario are considered rare sugars. If we can produce rare sugars as we wish, it is expected that various more useful biomaterials will be created by using them as raw materials. Thanks to the pioneering research of the Izumori group in the 1990′s, and to a few other investigations by other groups, almost all monosaccharides including l-sugars can now be produced by combining both chemical and enzymatic approaches. After briefly giving an overview of the origin of elementary hexoses and the current state of the rare sugar production, we will look ahead to the next generation of monosaccharide research which also targets glycosides including disaccharides.